A review on recent developments in structural modification of TiO2 for food packaging applications. (September 2022) - Kodithuwakku, Piyumi; Jayasundara, Dilushan R.; Munaweera, Imalka; Jayasinghe, Randika; Thoradeniya, Tharanga; Weerasekera, Manjula; Ajayan, Pulickel M.; Kottegoda, Nilwala
Abstract: Structural modification of titanium dioxide has offered a novel template to develop advanced functional materials which demonstrate visible light photocatalytic activity. There had been many attempts to modify the band gap of TiO2 in order to realize its potential as an antimicrobial material in food coatings and packaging. This review gathers most recent advancements of developing TiO2 based functional nanohybrids which include doping with metals, non-metals, co-doping, and development of hybrids with 2-D nanomaterials. In particular, nanohybrids prepared with of TiO2 with graphene incorporation has opened up a novel platform to reduce the band gap while minimizing the inherent drawback of electron pair recombination in TiO2 . In this review, critical analysis of the recent literature on the mechanisms involved in structural modifications are discussed broadly and the electronic and functional properties of resulting materials are presented with a greater scientific depth. In addition, the available structural modification techniques have been compared with a particular emphasis on food preservation and post-harvest loss mitigation applications. More importantly, an outlook on the industrial applications, future directions and challenges have been suggested and discussed. Graphical abstract: Image 1